1993
DOI: 10.1038/npp.1993.17
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of the Light Visor for Seasonal Affective Disorder: No Difference in Efficacy Found Between Two Different Intensities

Abstract: Fifty-five patients with winter seasonal affective disorder (SAD) were treated with a light visor, a newly developed ,mabie light-delivery system, in a controlled parallel agn. A dim (400 lux) visor was compared with a Wight (6000 lux) visor for either 30 or 60 minutes in the .oming for 1 week. Response rates for these two IrtItments were 36% and 56%, respectively; the duration � treatment sessions did not affect outcome. There was lEY WORDS: Seasonal affective disorder; Phototherapy; light; Circadian rhythms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 7 publications
2
32
0
Order By: Relevance
“…For example, the incidence of SAD in latitudes of [45][46][47][48][49][50] o or higher is over 10% compared to latitudes lower than 30 o , where the prevalence is around 1%. 42 As in atypical depression of those who have SAD, 60% to 90% are women, and it occurs more frequently in younger people, often beginning when the person is at his/her twenties. 43 Many of the symptoms of winter depression (e.g.…”
Section: Seasonal Affective Disorders (Sad)mentioning
confidence: 99%
“…For example, the incidence of SAD in latitudes of [45][46][47][48][49][50] o or higher is over 10% compared to latitudes lower than 30 o , where the prevalence is around 1%. 42 As in atypical depression of those who have SAD, 60% to 90% are women, and it occurs more frequently in younger people, often beginning when the person is at his/her twenties. 43 Many of the symptoms of winter depression (e.g.…”
Section: Seasonal Affective Disorders (Sad)mentioning
confidence: 99%
“…Because not all research supports morning light therapy over evening or dual morning-evening administration, Rosenthal et al (1993) suggested that light therapy may be important because it increases the overall number of photons reaching the retina. The essence of the photon-count hypothesis is that shorter photoperiods and/or less intense light in the winter result in an insufficient dose of light (i.e., fewer photons) to the retina in SAD-vulnerable individuals (Rosenthal et al, 1993).…”
Section: Light Therapy and The Photon-counting Hypothesismentioning
confidence: 99%
“…The essence of the photon-count hypothesis is that shorter photoperiods and/or less intense light in the winter result in an insufficient dose of light (i.e., fewer photons) to the retina in SAD-vulnerable individuals (Rosenthal et al, 1993).…”
Section: Light Therapy and The Photon-counting Hypothesismentioning
confidence: 99%
“…It may be that the methodology of these two studies has resulted in an inflated figure as both defined cases using the seasonality score on the Seasonal Pattern Assessment Questionnaire (SPAQ; Rosenthal et al, 1984)rather than DSM criteria. The SPAQhas also been used to demonstrate that in the USA prevalence of SAD rises with increasing latitude, which supports the hypothesis that environmental light conditions are important in its aetiology (Rosen et al, 1990).…”
Section: Epidemiologymentioning
confidence: 99%
“…Clinical assessment may be augmented by use of the SPAQ (Rosenthal et al, 1984). This is a self-rated questionnaire which assesses the degree of seasonal variation of mood symptoms and determines at which time of year symptoms are at their worst.…”
Section: Clinical Assessmentmentioning
confidence: 99%